Operational risk and resilience - Frost, Chris (Butterworth-Heinemann, 2000)
Well publicised failures in risk management have appeared with shocking frequency over the past few years. Affected firms can suffer significant commercial damage or even bankruptcy as a result. Only now is there a growing realisation that risk management is a key management responsibility. This book will help turn your firm into a 'risk aware' organization which will be able to avoid catastrophic loss. It will also enable senior management to make better strategic and operational decisions, thanks to an informed understanding of business hazards. * An insightful guide to one of the key topics of modern strategic and operational management, written by a team of expert risk management professionals. * Learn about the application of operational risk management to a wide range of market sectors, including commercial, retail and investment banking, investment management, insurance, the energy industry, telecommunications, manufacturing and logistics. * Case studies and worked examples from around the world, including North America, Western Europe, South East Asia and Latin America. Case studies from a wide cross section of different firms and markets are used to explain how to define, analyse and control operational risk. An insightful guide to one of the key topics of modern strategic and operational management, written by a team of expert risk management professionals. Learn about the application of operational risk management to a wide range of market sectors, including commercial, retail and investment banking, investment management, insurance, the energy industry, telecommunications, manufacturing and logistics. Case studies and worked examples from around the world, including North America, Western Europe, South East Asia and Latin America.
Includes bibliographical references and index. - Print version record
Keywords: Risk management; Operational risk; Risk Management; Gestion du risque; Risque opérationnel; risk management; BUSINESS & ECONOMICS; Insurance; Risk Assessment & Management